The impact of video integrated with Bloom’s taxonomy on the improvement of English-speaking performance - Butarbutar, Ranta; Leba, Seli Marlina Radja; Sauhenda, Angla F (Universitas Muhammadiyah Sidoarjo, 2022)
Speaking has an essential role in students’ performance in the English language subject. This study aims to investigate 30 English language students who are given video in the experimental class. The results show that there is an improvement of participants’ English-speaking performance which is indicated by the increase of scores between pre-test and post-test through four speaking components, such as fluency, precision, lexical, and syntactical. The most significant increase is found in the precision aspect with a pre-test value of 1.00 and a post-test value of 3.07. The results also reveal that both written and verbal communication can be improved by using the method of video integrated with Bloom’s taxonomy. However, the limited participants of the study and the length of drilling speaking are confirmed as the limitation of the study. Besides, it implies video integrated taxonomy Bloom for reducing anxiety in learning speaking and classroom activities research (CAR) investigation are recommendations for future study. HIGHLIGHTS: Video integrated with Bloom’s taxonomy implies the development of linguistics and intercultural communication competence simultaneously. Video facilitates learners to improve meaning and lexical complexity The more learners practice speaking with video integrated with Bloom’s Taxonomy, the better their critical thinking.